Construction of the profile of graduation: proposal for the educational initial training in Chile - Medina-Pérez, Jessica (2021)
At present, the graduation profiles are considered of great importance, since they delineate the training that will be delivered in each career, however, we find a variety of elements in them, some very complete and others with few skills mentioned especially, in the careers pedagogy, as noted in this study. The following research proposes the elements that should be considered for the construction of graduation profiles of future teachers, based on a bibliographic review and the main Educational Policies of Chile. The graduation profiles are fundamental for the construction of networks and study programs, likewise their correct elaboration is crucial for the consideration of the teacher model that we want for the country, which must be aligned with the demands of society, the current Educational Policies and successful international experiences. This work proposes an graduation profile for teachers, oriented and focusing competencies for Initial Teacher Training, thus outlining a teacher model, being constituted by: a common global competence, generic or transversal competences separated by axes, competences of the discipline and competences of the university seal. This work proposes a graduation profile for professors and it have a proposal seeks to contribute to orienting, targeting and enhancing the Educational Policies for Initial Teacher Training, both at the regional and national levels, achieving an exit profile for teachers and outlining a teacher model for the country.